2022
DOI: 10.3389/fimmu.2022.861545
|View full text |Cite
|
Sign up to set email alerts
|

Human Melanoma-Associated Mast Cells Display a Distinct Transcriptional Signature Characterized by an Upregulation of the Complement Component 3 That Correlates With Poor Prognosis

Abstract: Cutaneous melanoma is one of the most aggressive human malignancies and shows increasing incidence. Mast cells (MCs), long-lived tissue-resident cells that are particularly abundant in human skin where they regulate both innate and adaptive immunity, are associated with melanoma stroma (MAMCs). Thus, MAMCs could impact melanoma development, progression, and metastasis by secreting proteases, pro-angiogenic factors, and both pro-inflammatory and immuno-inhibitory mediators. To interrogate the as-yet poorly char… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 71 publications
0
24
0
Order By: Relevance
“…Mast cells may be immunoregulatory by affecting complement C3-related pathology, as suggested in basal cell carcinoma [reviewed in ( 7 )]. Recently, melanoma-secreted TGF-b and IL-1b were shown to upregulate C3 expression in melanoma-associated mast cells ( 40 ). Interestingly, chymase controls C3 effects by degrading C3, which has been reported in cutaneous vasculitis ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mast cells may be immunoregulatory by affecting complement C3-related pathology, as suggested in basal cell carcinoma [reviewed in ( 7 )]. Recently, melanoma-secreted TGF-b and IL-1b were shown to upregulate C3 expression in melanoma-associated mast cells ( 40 ). Interestingly, chymase controls C3 effects by degrading C3, which has been reported in cutaneous vasculitis ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…A similar association, though controversial, has been reported for breast [ 75 , 88 , 89 , 90 , 91 , 92 ], lung [ 93 , 94 , 95 ], and prostate cancer [ 96 , 97 ]. Furthermore, recent studies showed that human melanoma-associated Mast Cells characterized by an upregulation of the complement component C 3 correlates with poor prognosis [ 98 ].…”
Section: Mast Cell-targeted Strategies In Cancer Therapymentioning
confidence: 99%
“…As highlighted in recent reviews, the role of MCs in tumor development and progression is less straightforward and depends on tumor type and stage [4][5][6]. MCs accumulate in non-hematopoietic cutaneous malignancies, including basal cell carcinoma, squamous cell carcinoma, and melanoma [7,8]. Given the highly variable roles of MCs in different types of tumors, this review is focused specifically on the role of MCs in melanoma.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have sought to define roles for MCs in melanoma progression with conflicting results, depending on the parameters of MC activation evaluated, the stage of melanoma and the model utilized to investigate MC function. Transcriptome and predictive modeling studies link intratumoral MCs with poor prognosis, metastasis, and resistance to co-stimulatory blockade [7,[12][13][14][15][16][17]. Reduced metastasis has consistently been reported in mouse models in which melanomas are intravenously transplanted into mice fully deficient in MCs (Kit Wsh/Wsh ), or mice in which connective tissue type MCs are constitutively or transiently depleted [18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation